Nauczyciel w kontekście przemian w systemie kształcenia: stan obecny i oczekiwane kierunki zmian - Szott , Michał (Studia Edukacyjne, 2020)
Contemporary pedeutology constantly strives to determine the direction of the necessary changes in the educational system as regards the proper preparation of teachers to work in this profession. This is a department of pedagogy dealing with issues related to the teacher teacher. The most important research subjects in the fieldof pedeutologists’ interests are the personality of the teacher, the selection of suitable candidates for the job as a teacher, the training and improvement of the teaching staff. Previously, these problems were mainly dealt with in pedagogical, psychological and sociological approaches.Literature of the subject presents the personality of the student and the teacher as the essential com-ponents of the educational process. Newly published works on pedagogical themes, highlighting the increasing importance of teaching function in the education system, are emerging. Its role seems to be of particular importance when working with a child with special educational needs.From a historical point of view, the teacher’s function has changed a lot over the course of evolution. This indicates that with the passage of time waiting for teachers gradually increased. Contemporary educators are a very broad professional group, having their own way of preparing for the profession, and its interests are watched out by trade unions. The demands placed on the teacher today are very high, since he is mainly expected to shape the pupil’s personality (the process of education), not just the transfer of knowledge (the teaching process). Increasingly, the role of the school, which aims to be both an educator and an educator, imposes new tasks and responsibilities on the teacher. This makes us more and more often meet in pedagogy with the term „teacher-educator”, which refers to both aforementioned functions. We can also include other teacher functions such as tutor, leader, animator, organizer, didactic-educational process researcher, expert, therapist.It can be observed that a new structure of the personality of the educator is slowly emerging. This is due in part to the nature of man, his subjectivity in relation to the environment in which he lives. It is a unit that is constantly being created and created. Similarly, the profession of the teacher requires him to constantly adapt to changes in the education system and modern education. He should represent the personality in this matter effectively, and his morals and personal culture should contribute to the success of working with his charges. Such a structure of teacher personality consists of elements such as: worldview, interests, motives, temperament, abilities, intelligence, appropriate character, striving for self-improvement (self-mastery), self-conscience.